Education for All, the North/South dilemma and decolonising the minds - Carvalho, C. (Globalisation, Transnationalism and Development research programme, 2017)
Invited conference at the Globalisation, Transnationalism and Development research programme (GTD), Maastrich Universtiy on “Education for All, the North/South dilemma and decolonising the minds”, 08-03-2017 (https://www.maastrichtuniversity.nl/globalisation-transnationalism-and-development)